Study of Ridostin Pro and Poly(I:C) as adjuvants that enhance the immunogenicity of an antitumor vaccine - A. V. Ponomarev; P. V. Tsarapaev; M. A. Baryshnikova; Z. A. Sokolova; A. A. Rudakova; M. V. Mironova; D. V. Gusev; G. M. Levagina; E. D. Danilenko; V. S. Kosorukov (Сибирский онкологический журнал)
Aim of the study: to compare the antitumor efficacy and immunogenicity of vaccines with the same antigens but different adjuvants: Ridostin Pro or Poly(I:C); to evaluate the effect of Ridostin Pro and Poly(I:C) on the cytokine profile of serum and the immunophenotype of mouse spleen cells. Material and Methods. To evaluate the antitumor efficacy of vaccines with different adjuvants, two transplantable tumor lines were used: melanoma B16-F10 and EG 7-OVA lymphoma (expressing ovalbumin) for C57BL/6 mice. Against melanoma B16-F10, vaccination with the peptide TRP2 180–188 with the studied adjuvants was performed in a mixed (preventive/therapeutic) and therapeutic regimens. Ovalbumin with adjuvants was vaccinated against EG 7 lymphoma in a therapeutic mode. The immunogenicity of vaccines with different adjuvants in mice without tumors was evaluated by the ELISPOT method. In this case, the peptide TRP2 180–188 and the protein ovalbumin also served as antigens. The cytokine profile of blood serum and changes in the immunophenotype of mouse spleen cells after administration of Ridostin Pro or Poly(I:C) were studied using flow cytometry. Results. In the B16-F10 model, vaccination in a mixed mode protected mice from tumor formation, and the mice lived for more than 100 days. For B16-F10 and EG 7, vaccination in the therapeutic mode led only to inhibition of tumor growth. Ridostin Pro and Poly(I:C) showed a similar ability to develop specific immunity to the peptide TRP2 and ovalbumin. Ridostin Pro increased cytokine levels in the blood serum of mice more strongly than Poly(I:C). Both drugs caused similar changes in the immunophenotype of spleen cells, but Ridostin Pro increased the number of CD 69+ T cells more strongly than Poly(I:C). Conclusion. The comparison of two drugs as adjuvants for antitumor vaccines showed that the domestic drug Ridostin Pro did not inferior in effectiveness to Poly(I:C) on mouse models. In this regard, Ridostin Pro can be considered as a promising adjuvant for antitumor vaccines and deserves further study.